Mercury concentration data from Matang Mangrove Forest Reserve, Malaysia - Wolswijk, Giovanna (Data Brief, 2020)
This paper presents the results of mercury analysis on 786 abiotic (surface sediments) and biotic (plant and animal tissues) samples collected from 10 sites at Matang Mangrove Forest Reserve in Peninsular Malaysia. Sediment samples were collected at the surface level from both river bank and forest understory. Whereas plant tissues obtained from Rhizophora apiculata Blume and Rhizophora mucronata L. consisted of leaves (in four stages namely young, mature, senescent and decomposing), bark and roots (divided into xylem, cortex and epidermis), the animal samples were represented by muscle tissue of the gastropod Cassidula aurisfelis Bruguière and the cockle Tegillarca granosa L. The mercury concentration measurements were obtained through a cold vapor atomic absorption spectrometer. The core data have been analysed and interpreted in the paper “Distribution of mercury in sediments, plant and animal tissues in Matang Mangrove Forest Reserve, Malaysia” [1].